Brückenbauer Großbritannien, die deutsche Frage und die Blockade Berlins 1948-1949 - Mauer, Victor (Veröffentlichungen des Deutschen Historischen Instituts London/ Publications of the German Historical Institute London, 2018)
On the occasion of the 70th anniversary of the Soviet blockade, a well-sourced study of British crisis policy is being published for the first time, and it yields surprising new insights. Victor Mauer's work revises our notions of British (and thus Western) policy during the Berlin blockade. It also suggests the need to re-evaluate the history of Britain's German policy, without which we cannot understand the crisis policy.